Perancangan dan Implementasi Aplikasi Penjadwalan Mengajar Guru Berbasis Web Menggunakan Metode R&D dan Agile - Ria Ester; Yuliana (OKTAL : Jurnal Ilmu Komputer dan Sains, 2026)
Teacher scheduling is an important part of educational activity management. Scheduling that is still performed manually using Excel templates creates several problems, including a relatively long preparation time, potential scheduling conflicts, difficulty identifying teacher availability, and delays in adjusting schedules when changes or substitute teachers are required. This study aims to design and implement a web-based teacher scheduling application to improve the efficiency and effectiveness of schedule management. The research uses the Research and Development (R&D) method with an Agile Study approach. Data were collected through observation, interviews, and literature study. The system was developed using PHP, HTML, CSS, JavaScript, Bootstrap, and MySQL. The implementation produced a system capable of managing teacher data, class data, subjects, teaching schedules, teacher availability, substitute teachers, and schedule reports in PDF and Excel formats. Black Box Testing on the reported scenarios resulted in passed status, while White Box Testing was used to evaluate the program logic flow. User evaluation involving 20 respondents and 15 questions resulted in 271 Yes responses out of 300 responses, or 90.33%, placing the system in the Highly Feasible category. The results indicate that the application supports more structured schedule management and facilitates schedule adjustments and substitute teacher assignments.